Severe multiple rabid dog bite injuries in a child in central China: Continuous 10-year observation and analysis on this case - Zhenggang Zhu; Shichun Huang; Sha Lu; Man Zhang; Shengli Meng; Quan Hu; Yuan Fang (Taylor & Francis Group, 2020)
Dog bites are common in rural areas of underdeveloped countries or regions, affecting persons of different ages. Suspected rabid dog bites will lead to more severe outcomes, especially in children because injuries often occur on their heads and faces that are highly innervated parts of the body. In such circumstances, immediate and complete post-exposure prophylaxis (PEP) will be essential, though vaccine hesitancy is a problem. Herein, we report a 4-y-old girl who was seriously bitten by a confirmed rabid dog in rural China. Multiple lacerations and punctures distributed on her head, neck, face, extremities, and back after being bitten. It was in question that surgery or PEP should be performed in priority when the dog was not confirmed rabid at first, but considering the risks of rabies, immediate PEP was provided to her, along with immunogenicity tests to ensure an adequate protective immune response. Because of the severity of her injuries, medical practitioners suggested her parents to bring her to take immunogenicity tests in 1-, 5-, and 10-y intervals to ensure adequate rabies virus-neutralizing antibodies (RVNA) titers. Her parents had a good preference for medical advices, and in the 10-y interval, it was found that her RVNA titer was below protection level, so a booster vaccination was given to her, and 14 d after that, according to immunogenicity test, RVNA titer arose quickly above the protection level.